2010
DOI: 10.1007/s00726-010-0765-2
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of the ubiquitin–proteasome proteolysis system by amino acids and insulin involves the adenosine monophosphate-activated protein kinase and mammalian target of rapamycin pathways in rat hepatocytes

Abstract: The purpose of this work was to examine whether changes in dietary protein levels could elicit differential responses of tissue proteolysis and the pathway involved in this response. In rats fed with a high protein diet (55%) for 14 days, the liver was the main organ where adaptations occurred, characterized by an increased protein pool and a strong, meal-induced inhibition of the protein breakdown rate when compared to the normal protein diet (14%). This was associated with a decrease in the key-proteins invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…4c). As PRAS40-KD inhibits mTORC1 signalling, and inhibition of mTORC1 activity has been linked to increased protein degradation by increased activity of the ubiquitinproteasome system [30,31], we next examined whether mRNA expression of the muscle-specific E3-ligases FBXO32 and MURF1, which are increased in mice heterozygous for mTOR [30], is affected by PRAS40-KD. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4c). As PRAS40-KD inhibits mTORC1 signalling, and inhibition of mTORC1 activity has been linked to increased protein degradation by increased activity of the ubiquitinproteasome system [30,31], we next examined whether mRNA expression of the muscle-specific E3-ligases FBXO32 and MURF1, which are increased in mice heterozygous for mTOR [30], is affected by PRAS40-KD. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One may speculate that the effects of PRAS40-KD on the proteasome result from inhibition of mTORC1 activity. In primary rat hepatocytes, short-term pharmacological inhibition of mTOR was found to reverse the inhibition of the ubiquitin-proteasome pathway by insulin and amino acids [31]. Furthermore, skeletal muscle of mTOR-heterozygous mice displays elevated levels of the E3 ligases FBXO32 and MURF1 [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, the ubiquitin-proteasome system likely confounds this investigation, as this pathway can also be inhibited by insulin and amino acids. 653 In addition, multiple disease states have been associated with an altered activity of the ubiquitin-proteasome system, further complicating the use of the amino acid exchange rate as a marker of autophagy. 654 When analyzing basal autophagic level in vivo using GFP-LC3 transgenic mice, 126 one pitfall is that GFP-LC3 expression is driven by the cytomegalovirus enhancer and β-actin (CAG) promoter, so that the intensity of the GFP signal may not always represent the actual autophagic activity, but rather the CAG promoter activity in individual cells.…”
mentioning
confidence: 99%
“…HP diets can have a profound impact on the functioning of the liver because of its central role in amino acid and protein metabolism (Chotechuang et al 2011), with demonstrated reductions in serum levels of glycine and cysteine (Cys), 2 amino acids used for homocysteine (Hcy) clearance (Holecek and Kovarik 2011;Ohuchi et al 2009). Elevated serum Hcy levels have been observed with long-term HP feeding in some studies (Wakefield et al 2011;Xiao et al 2013), but not in others (Noakes et al 2005), and this is of interest because the serum Hcy level is being considered as an independent risk factor for many cardiovascular diseases (Refsum et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated serum Hcy levels have been observed with long-term HP feeding in some studies (Wakefield et al 2011;Xiao et al 2013), but not in others (Noakes et al 2005), and this is of interest because the serum Hcy level is being considered as an independent risk factor for many cardiovascular diseases (Refsum et al 1998). Liver enlargement in response to HP diets has been observed in rats (Chotechuang et al 2011) and mice (Hammond and Janes 1998), but no adverse effects on liver function were observed in overweight and obese human subjects consuming HP diets for 1 year (Li et al 2010). Studies in mice and humans have shown prevention and reversal of hepatic steatosis (Bortolotti et al 2009;Garcia-Caraballo et al 2013) and reduction in inflammation with HP diets (Garcia-Caraballo et al 2013).…”
Section: Introductionmentioning
confidence: 99%